Perspectives on the Internationalisation of Higher Education - Law, David, editor; Hoey, Michael, editor (New York :bRoutledge, 2018)
Internationalisation of the contemporary university has become a pervasive and powerful development theme during the past three decades. In many countries, higher education is now a major export industry. The UK has longstanding experience of overseas student recruitment, international partnerships between universities and trans-national education. It has led the world in the development of the quality assurance of overseas activities. This collection of essays brings together articles published in the journal of the UK Association of University Administrators (AUA). Several of the pieces are members of AUA whilst others are by authors who work in other countries. Overall, in this volume, there is a practitioner focus that provides the reader with lessons learnt by those with experience of implementing policies to promote the internationalisation of higher education. We are interested both in how universities can manage the challenges that they face, and in how the experience of students can be enhanced by participation in internationalisation. Because the AUA has an enduring commitment to the professionalization of management and administration, readers of this anthology will find accessible, focussed and brief articles that are solution-oriented. This book was originally published as a special issue of Perspectives: Policy and Practise in Higher Education.